Comparison of bacterial removal from dentinal tubules with different irrigant agitation techniques: An in vitro study - Mohammad I. Al-Obaida; Reina Moukaddem; Ziyad Allahem; AbdulAziz AbdulWahed; Faisal A AlOnaizan; Ebtissam M. Al-Madi (Elsevier, 2019)
Aim: This investigation was conducted to assess the ability of various irrigant agitation devices to eradicate Enterococcus faecalis from the dentinal tubules of extracted teeth. Methodology: Fifty roots of extracted human teeth were instrumented to size 30 k with a 0.04 taper. The roots were autoclaved and then injected with E. faecalis. The canals were assigned to one of four intervention groups and disinfected using (A) standard needle irrigation, (B) EndoUltra® Ultrasonic Activator, (C) the EndoActivator system, or (D) EDDY sonic activation and to two control groups that were (E) treated with saline and (F) not inoculated with any bacteria. The roots were split in half, dyed with a LIVE/DEAD Back Light Bacterial Viability Kit, and then scanned with a confocal laser scanning microscope (CLSM) to identify live/dead bacteria in the dentinal tubules. Results: CLSM images revealed differences among the groups. Both the EndoUltra® Ultrasonic Activator group and the EDDY group had a combination of dead and live bacteria, while the EndoActivator group had mostly dead bacteria, in contrast to single needle irrigation which had mostly live bacteria. Activation of the irrigating solution resulted in more dead bacteria than standard needle irrigation at the coronal, middle, and apical parts of the roots. Overall, the EndoActivator system was superior to all other techniques in reducing live bacteria within the root canal. Conclusion: Activation of sodium hypochlorite with sonic and ultrasonic systems dramatically reduced live bacteria contamination in the dentinal tubules of infected root canals. Keywords: Irrigation, EndoUltra® ultrasonic activator, EndoActivator, EDDY sonic activation, Confocal laser scanning microscopy, Dentinal tubules